Globalization and the environment : greening global political economy - Kütting, Gabriela, 1967- (State University of New York Press, 2004)
Annotation. This groundbreaking study brings together economic globalization and the environment as never before. Gabriela Kutting argues for an "eco-holistic" approach that merges social, political, economic, and environmental analysis, so that a globalizing political economy may be understood in relation to environmental and social concerns. Key to this merging are the historical dimension of environmental-societal relations, the concept of consumption, and the concept of equity. To illustrate the utility of the eco-holistic approach, Kutting draws out the linkages between social and environmental degradation in West Africa, environmental and economic policies in the North, and the shopping habits of individual consumers, using cotton agriculture and the globalizing political economy of textiles as a case study
Keywords: Environmental economics.; Sustainable development.; Globalization.; Économie de l'environnement.; Développement durable.; Mondialisation.; sustainable development.; globalism.; BUSINESS & ECONOMICS -- Development -- Sustainable Development.; BUSINESS & ECONOMICS -- Environmental Economics.; Environmental economics; Globalization; Sustainable development